MAPPING THE INFLUENCE: A CONCEPTUAL MODEL OF BRAND REPUTATION, INFLUENCER MARKETING, ORGANIZATIONAL AGILITY, STRATEGIC LEADERSHIP, AND BUSINESS PERFORMANCE - Andriani, Ria; Heirunissa, Heirunissa; Harun, Muhamad; Herlan, Hasta (Universitas Muhammadiyah Tangerang, 2025)
This study proposes a conceptual model that integrates brand reputation, influencer marketing, and organizational agility in driving business performance, with strategic leadership as a moderating variable. The study is motivated by the need for organizations to adapt to rapid market changes. The method employed is a systematic review of journal articles indexed in SINTA, Google Scholar, and Scopus, as well as relevant industry reports. The results indicate that brand reputation and influencer marketing have a positive influence on organizational agility, which in turn mediates the improvement of business performance through enhanced responsiveness and operational efficiency. Furthermore, strategic leadership strengthens the relationship between organizational agility and business performance by effectively leveraging market dynamics. The findings highlight the importance of synergy between brand reputation management, ethical implementation of influencer marketing, and the reinforcement of organizational agility to achieve sustainable business performance, particularly among SMEs in Indonesia. The study's limitation lies in its reliance on secondary data, suggesting that future research should involve field studies for model validation.